2019
DOI: 10.1002/jcb.28984
|View full text |Cite
|
Sign up to set email alerts
|

miR‐148‐3p and miR‐152‐3p synergistically regulate prostate cancer progression via repressing KLF4

Abstract: Background miR‐148‐3p and miR‐152‐3p as the tumor suppressors have been reported in various cancer types. Our study is aimed to discuss the synergistic effect of miR‐148‐3p and miR‐152‐3p in prostate cancer (PCa). Methods Bioinformatics algorithm and luciferase reporter assays were used to verify whether miR‐148‐3p and 152‐3p could bind with the 3′‐untranslated region (3′‐UTR) of Kruppel‐like factor 4 (KLF4). PCa cell growth in vivo was analyzed using the mouse xenograft tumor model. Results miR‐148‐3p and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…Intriguingly, OLA had the ability to reverse IL‐1β‐induced down‐regulation of miR‐148‐3p. Published studies have reported that the functions of miR‐148‐3p are focused on antineoplastic activity . The present study is the first to indicate that miR‐148‐3p might be involved in chondrocyte dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…Intriguingly, OLA had the ability to reverse IL‐1β‐induced down‐regulation of miR‐148‐3p. Published studies have reported that the functions of miR‐148‐3p are focused on antineoplastic activity . The present study is the first to indicate that miR‐148‐3p might be involved in chondrocyte dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…Some studies have revealed that miR-148 and miR-10 inhibited the proliferation of different types of cells. For example, miR-148-3p inhibited the growth of glioblastoma by targeting DNMT1 and PCa cell growth in vivo [44,45]. It was also found that miR-148a could suppress human renal cell carcinoma malignancy by targeting AKT2 [46].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the protein expression of RHOA was significantly negatively correlated with miR-154-3p and miR-487-3p expression in 63 thyroid cancer tissues. miRs play crucial roles in modulating gene expression via post-transcriptional repression [25,26]. In fact, single miR can modulate multiple target genes, in contrast with that, one gene can be regulated by multiple miRs [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…miRs play crucial roles in modulating gene expression via post-transcriptional repression [25,26]. In fact, single miR can modulate multiple target genes, in contrast with that, one gene can be regulated by multiple miRs [25,26]. For example, miR-143 and miR-145 gain-of-function synergistically suppress cell proliferation and invasion in breast cancer through the repression of ERBB3 protein expression [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation